GDP Growth in the German Federal States: Large Differences, but Little Reliability of the Data - Roland Döhrn (Wirtschaftsdienst)
Abstract In March 2021, the first release of regional national accounts in 2020 was published. Due to the coronavirus crisis, GDP shrank in all federal states, but with significant differences. However, the data must be interpreted with caution. The regional national accounts are subject to large revisions, which may change the position of a federal state in a growth ranking considerably. In nine out of 17 years analysed, there is no significant correlation between the ranking of the states in the initially released data and in the final data. Thus, methods of regional national accounting should be improved to reduce revisions.